Mobile commerce in Singapore. - Leow, Seok Wei. (2008)
This research study focuses on the business-to-consumer aspect of mobile commerce: the awareness of mobile commerce, the willingness to adopt mobile commerce, the characteristics of the potential adopters, the motivations and deterrents of mobile commerce and the future potential of mobile commerce.In all,this research hopes to provide useful information to businesses.